The Use and Strength of the ‘al-Asl fi al-Mu’amalah al-Ibahah Method In the DSN-MUI Fatwa in Indonesia - Hidayat Hidayat (International Journal of Islamic Thought and Humanities, 2023)
The number of promotions and requests to invest in Islamic financial institutions has made policymakers, especially the DSN-MUI, work harder to make regulations that are easy to comply with sharia and fatwas that attract public interest to practice them. This study aims to analyze the rules of fiqh (especially al-asl fi al-muamalat al-ibahah) used by DSN-MUI by comparing them with previous fiqh books. This study finds that the choice of this rule as one of the most dominant rules is because the rule has a very broad scope and is easy to use with its arguments. Also, the DSN-MUI fatwa is overall quite good but nevertheless still needs improvement.